Analisis Pengaruh Faktor Fundamental terhadap Harga Saham pada Perusahaan yang Konsisten Terdaftar di Jakarta Islamic Index - Fadhillah Syahba Adrisa; Ade Ali Nurdin; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
This study aims to determine the effect of fundamental factors on the stock prices of companies that are consistently listed on the Jakarta Islamic Index (JII) during the 2014-2018 period, either partially or simultaneously. Fundamental factors consist of financial ratios, namely Current Ratio (CR), Debt to Equity Ratio (DER), Earning Per Share (EPS), and Return On Equity (ROE), as well as macroeconomic variables represented by Inflation and Bank Indonesia Interest Rates ( BI Rate). The results showed that partially the ROE variable had a significant effect on JII's stock price, while CR, DER, EPS, Inflation, and BI Rate had a negative and insignificant effect on JII's stock price. Simultaneously the variables CR, DER, EPS, ROE, Inflation, and BI Rate have a significant effect on JII's stock price.